2011
DOI: 10.1038/aps.2010.207
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological mechanisms of sophocarpine as a potential antiarrhythmic agent

Abstract: Aim: To examine the electrophysiological effects of sophocarpine on action potentials (AP) and ionic currents of cardiac myocytes and to compare some of these effects with those of amiodarone. Methods: Langendorff perfusion set-up was used in isolated guinea pig heart, and responses to sophocarpine were monitored using electrocardiograph. Conventional microelectrode, voltage clamp technique and perforated patch were employed to record fast response AP (fAP), slow response AP (sAP) and ionic currents in guinea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Sophocarpine (SPC) (Figure A) is one of the major bioactive compounds derived from the natural plant Sophora flavescens , which is widely distributed in Russia, Japan, India and China. Anti‐inflammatory, anti‐tumour, anti‐allergic, cardioprotective and neuroprotecive effects have been demonstrated in previous studies (Yang et al, ; Yifeng et al, ; Gao et al, ; Wang et al, ; Li et al, ; Zhang et al, ). SPC can inhibit LPS‐induced inflammation in RAW 264.7 cells via the NF‐κB and MAPKs signalling pathways (Gao et al, , ).…”
Section: Introductionmentioning
confidence: 68%
“…Sophocarpine (SPC) (Figure A) is one of the major bioactive compounds derived from the natural plant Sophora flavescens , which is widely distributed in Russia, Japan, India and China. Anti‐inflammatory, anti‐tumour, anti‐allergic, cardioprotective and neuroprotecive effects have been demonstrated in previous studies (Yang et al, ; Yifeng et al, ; Gao et al, ; Wang et al, ; Li et al, ; Zhang et al, ). SPC can inhibit LPS‐induced inflammation in RAW 264.7 cells via the NF‐κB and MAPKs signalling pathways (Gao et al, , ).…”
Section: Introductionmentioning
confidence: 68%
“…The most promising ones were dauricine , an alkaloid from Asiatic Moonseed Rhizome , and sophocarpine , an alkaloid from Sophora flavescens , that inhibit cardiac transmembrane Na+, K+, and Ca2+ ion currents thus prolonging the action potential duration and effective refractory period. 51 , 52 The authors also warn on the possible synergistic interaction of certain herbal components (e.g., Hawthorn, Licorice and Ginseng) with cardiac glycosides.…”
Section: The Special Issue At a Glancementioning
confidence: 99%
“…It has also been found that Sophocarpine is an effective agent in the treatment of viral myocarditis for both its antiviral and antiarrhythmic properties ( Zhang et al, 2006 ). Furthermore, Sophocarpine has a therapeutic effect on liver protection in that it can alleviate liver fibrosis by suppressing both the activation of hepatic stellate cells and the proliferation of the activated hepatic stellate cells ( Yang et al, 2011 ). In spite of those experimental studies and case reports, little work has mentioned the effect of Sophocarpine on NK cell activity.…”
Section: Introductionmentioning
confidence: 99%